2019
DOI: 10.16965/ijar.2018.425
|View full text |Cite
|
Sign up to set email alerts
|

An Osteological Study on Nutrient Foramina of Human Dry Adult Ulna Bones

Abstract: Background: Nutrient artery is the major source of blood supply to long bones. This artery enters the shaft of the long bone through nutrient foramen. Vascular insults to the Ulna during fracture dislocation or during surgical correction of fracture may result in delayed healing or non-union of fracture.Materials and Methods: The present study was undertaken on 100 dry adult ulna bones of unknown sex (50 each of right and left sides) from Department of Anatomy, Gadag Institute of Medical Sciences, Gadag, Karna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 2 publications
1
5
0
Order By: Relevance
“…When the localization of the NF in the clavicle and humerus was examined, our results were similar to the results of previous studies (Table 3). Result of this study, most of the NF in the radius and ulna are localized in the middle 1/3 of the bone, while there are studies in the literature in which the NF is mostly localized in the proximal 1/3 of the bone (Table 3) (19,20). This strengthens the likelihood of differences between populations.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…When the localization of the NF in the clavicle and humerus was examined, our results were similar to the results of previous studies (Table 3). Result of this study, most of the NF in the radius and ulna are localized in the middle 1/3 of the bone, while there are studies in the literature in which the NF is mostly localized in the proximal 1/3 of the bone (Table 3) (19,20). This strengthens the likelihood of differences between populations.…”
Section: Discussionsupporting
confidence: 65%
“…We encountered the NF also in the interosseous border in the current study, differently from the literature (7,27). In the ulna we examined, the most common anatomic location of the NF was the anterior surface, as in previous studies (20,(24)(25)(26). While there are studies indicating the NF in the anterior border and medial surface of the ulna, we did not encounter the NF in the anterior border and medial surface in our study (27)(28)(29).…”
Section: Discussionmentioning
confidence: 98%
“…Most of the previous studies reached a consensus that the opening of the NF is towards the elbow. Nevertheless, Rangasubhe and Havaldar (16) observed 115 NF in their study and reported that 97% of NF were directed upper oblique, 2% lower oblique and remaining horizontally. Similar to the previous studies, the direction of all NF in the present study was also towards the elbow.…”
Section: Direction and Topography Of The Nutrient Foramenmentioning
confidence: 87%
“…Similar to the study of Ukoha et al ( 4), Azizi and Danish (1) indicated that most of the NF (80%) were located in the middle third, while the remaining (20%) were situated in the upper third of the ulna. Likewise, Rangasubhe and Havaldar (16) determined that 85.22% of NFs were in the upper third and 12.17% were in the middle third of the ulna. Priya et al (11) calculated that the mean FI was 35.83 ± 6.12 and reported that 40% of NF were present in the type 1 category and 60% in type 2.…”
Section: Direction and Topography Of The Nutrient Foramenmentioning
confidence: 94%
See 1 more Smart Citation